Batik Encim Pekalongan, Kehalusan Batik Gaya Cina Di Pesisir Jawa - Purnomo, Muhammad Arif Jati (Pendhapa, 2009)
Batik encim is the term used to be worn by married Chinese ladies. The term batik encim is very popular, especially for Javanese people in northern beach, such as Pekalongan. The existence of batik encim coincides with the trend of batik style that develops in Indonesia, especially in Java. The batik encim is usually the cloth or sarong. It has the function to be matched with the kebaya cloth. In this case, the batik encim style consists of decoration kind or pattern, making region, technique or making process and coloring. Batik encim appears as the expression of people of Chinese descent in coastal area by batik media. Kinds of decorations or patterns on batik encim are taken from the cultural background of Chinese descent, for example Hong bird, dragon, kilin, and butterfly with special coloring suitable with their desire. Visually the product quality of batik encim is very perfect, complicated and soft. The beauty of batik encim is without doubt. The making of batik encim takes a very long process and time: from pretreatment cloth, painting, coloring, and the last processing. Keywords : Batik encim, style, and motif